The Jack Pine: Preserving the Northern Ontario Landscape through Painting, Music, and Short Film - Prevost, Roxane (Intersections, 2016)
In her program note, Canadian composer Jocelyn Morlock explains that she was inspired by Tom Thomson’s 1916–17 painting, which depicts a Jack pine clinging to a rock on the edge of water, for her solo piano piece The Jack Pine (2010). Julian Beecroft later posted a short film of the Algonquin Park, accompanied by Morlock’s work. This article examines some of the intersections between the transition of colours in the painting and the harmonic colours of the music through voice-leading analysis, and some of the ways in which the music successfully depicts the different scenes of the short film.